Historical and legal overview of the State and Advocacy interaction within the system of human rights and freedoms protection (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article examines the interaction between the State and the Advocacy as a human rights protection organisation from the historical and legal perspective. At all times of its formation and development, the Advocacy has operated within a certain system of state and social relations and was called upon to promote the protection of human interests in accordance with the laws of the State in which it operated. The activities of the Advocacy have always been multifaceted, and therefore the article describes various methods of studying the interaction between the State and the Advocacy from the historical and legal perspective. The necessity of studying the interaction between the State and the Advocacy to refer to the legal documents of the past which regulated the activities of the Advocacy and its relationship with the State is emphasised.It is demonstrated that at all times the institution of human rights protection, which is now perceived as the Advocacy, has not acted in isolation, but has been a component of the society system, acting in accordance with the laws and in accordance with the procedure established by the State. The Advocacy functions in the unified legal system of the state together with the state authorities, central executive bodies and their local bodies and institutions, local self-government bodies, and civil society institutions. Therefore, when analysing the interaction between the state and the Advocacy, characterising the activities of the Advocacy in the protection of human rights and freedoms, it is necessary to consider the activities of the subjects of power in the protection of human rights and freedoms. Interaction between the State and the Advocacy is a social interaction.It is emphasized that in the process of social interaction, social, statutory, socio-legal actions of partners take place, and mutual adaptation of actions of each of them, which leads to the use of various research methods in the process of historical and legal review of interaction between the State and the Advocacy.